Assessment of Anti-bacterial Activity of (E)-2-(Naphthalen-1-yldiazenyl) Malononitrile Against Pathogens Bacteria. (Comprehensive Journal of Science, 2025)
(E)-2-(naphthalen-1-yldiazenyl) malononitrile (NDMN) was synthesized via a diazotization–coupling reaction and evaluated for its antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli. The compound showed strong, concentration-dependent antibacterial activity, with significantly higher efficacy against MRSA than E. coli, as confirmed by disc diffusion, MIC, and MBC assays. These results suggest that NDMN is a promising synthetic antimicrobial agent, particularly against Gram-positive resistant bacteria, and merits further biological and toxicity investigations.
Keywords: Azo compounds; Malononitrile; Antibacterial activity; MRSA, Escherichia coli.